An investigation of the L-shell X-ray conversion efficiency for laser-irradiated tin foils - Bailie, D; Hyland, C; Singh, R; White, S; Sarri, G; Keenan, F; Riley, D; Rose, S; Hill, E; Wang, F; Yuan, D; Zhao, G; et al. (IOP Publishing, 2019)
We have used the Shenguang II laser in third harmonic (351 nm) to investigate the emission of L-shell radiation in the 3.3–4.4 keV range generated using thin foils of Sn coated onto a parylene substrate with irradiation of order 1015 W cm−2 and nanosecond pulse duration. In our experiment, we have concentrated on assessing the emission on the non-laser irradiated side as this allows an experimental geometry relevant to experiments on photo-ionised plasmas where a secondary target must be placed close to the source, to achieve x-ray fluxes appropriate to astrophysical objects. Overall L-shell conversion efficiencies are estimated to be of order 1%, with little dependence on Sn thickness between 400 and 800 nm.